Audit sistem informasi pada pelayanan e-government pemerintahan desa menggunakan framework COBIT 5 - Septory, Dramendra; Andarwati, Mardiana (Universitas Merdeka Malang, 2023)
Suboptimal e-government implementation can make it difficult for people to get the information they need, as well as causing data security vulnerabilities. This research examines the implementation of service information system audits related to e-government using the COBIT 5 approach at the Oro-Oro Dowo Village Office, Malang City. The aim of this research is to determine the level of capability of the e-government service information system and identify potential improvements in information technology. The methods used involve observation, interviews, literature studies, and questionnaires. The research results show that information technology and e-government governance has not been managed well. The maturity level for implementing COBIT 5 in sub domains APO 02, 04, 07, 13, and variable Y is level 3 established process with several areas that require more attention in an effort to increase system efficiency and security. Recommendations are given to improve information technology governance, as well as monitoring so that it can support the development of a better public service system at the sub-district level. This research provides insight into the potential for improvements in e-government service information system audits at the local level.